Measurement of Mitochondrial pH In Situ. (April 2001) - Takahashi, Akiyuki; Zhang, Yingpei; Centonze, Victoria E.; Herman, Brian
In this article, we describe the advantages and disadvantages of procedures for monitoring mitochondrial pH in situ using optical microscopic techniques. The first method employs the combination of the fluorescent pH-sensitive indicator carboxy-SNARF and laser scanning confocal microscopy. Manipulation of the loading and post-loading conditions enables relatively specific accumulation of carboxy-SNARF into mitochondria. With the use of a mitochondrial-specific marker, mitochondrial pH can be accurately monitored. More recently, mitochondrial-targeted, pH-sensitive probes have been used to monitor mitochondrial pH. In particular, mitochondrial targeting of the yellow fluorescent protein (YFP) mutant of green fluorescent protein (GFP) combines the advantages of specific mitochondrial localization, high-fluorophore quantum yield, and extinction coefficient with an appropriate pKa for measuring mitochondrial pH. The use of dual-excitation ratiometry with mitochondrially targeted YFP increases the dynamic range of mitochondrial pH measurements and corrects for differences in the amount of expression of mitochondrially targeted YFP at the level of individual mitochondria.